The importance of palliative care in Duchenne muscular dystrophy: a reflection - Saha, Vasundhara (International Journal of Research in Medical Sciences, 2023)
Duchenne muscular dystrophy is a progressive disease involving early morbidity and mortality of children. Hence, it becomes essential to address the evolving issues comprehensively according to palliative care principles. Apart from physical issues, psychological, ethical and spiritual concerns affect the quality of life throughout the symptomatic period including the end of life. This case depicts the incomplete management of progressive physical issues as well as psychological, ethical and spiritual concerns of a ten-year-old child and his family. Lack of proper communication and inadequate knowledge about end-of-life care adversely impacts the quality of life of such patients. Understanding of Palliative Care principles helped to gain insight about the lacuna in clinical care of such patients. Knowledge and incorporation of Palliative Care principles is extremely important for any clinician dealing with progressive diseases like Duchenne Muscular Dystrophy and many more. Application of these principles has the potential to enhance the quality of life of patients and their caregivers significantly throughout the course of the disease.